2009
DOI: 10.1007/s00726-009-0246-7
|View full text |Cite
|
Sign up to set email alerts
|

High fat feeding and dietary l-arginine supplementation differentially regulate gene expression in rat white adipose tissue

Abstract: Dietary L-arginine (Arg) supplementation reduces white-fat gain in diet-induced obese rats but the underlying mechanisms are unknown. This study tested the hypothesis that Arg treatment affects expression of genes related to lipid metabolism in adipose tissue. Four-week-old male Sprague-Dawley rats were fed a low-fat (LF) or high-fat (HF) diet for 15 weeks. Thereafter, lean or obese rats continued to be fed their same respective diets and received drinking water containing 1.51% Arg-HCl or 2.55% L: -alanine (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
101
3
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 63 publications
8
101
3
2
Order By: Relevance
“…There is evidence for the participation of adjustment mechanisms between intrinsic and primary extrinsic afferent neurons and the central nervous system in addition to enzyme gene transcription mechanisms, and even gene expression, as speciϐi-cally reported for some amino acids, such as Arg & Gln (Fu et al 2005, Wang et al 2008, Jobgen et al 2009, Wu 2009.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…There is evidence for the participation of adjustment mechanisms between intrinsic and primary extrinsic afferent neurons and the central nervous system in addition to enzyme gene transcription mechanisms, and even gene expression, as speciϐi-cally reported for some amino acids, such as Arg & Gln (Fu et al 2005, Wang et al 2008, Jobgen et al 2009, Wu 2009.…”
Section: Discussionmentioning
confidence: 89%
“…They also regulate gene expression in highly speciϐic processes that involve the transfer of coded information from a gene to its product (RNA and/or protein). In mammals, research has shown that dietary supplementation with Arg and glycine (Gln) can increase the expression of antioxidant genes and reduce the expression of proinϐlammatory genes in the small intestine and adipose tissue (Fu et al 2005, Wang et al 2008, Jobgen et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Arginine is a conditionally essential amino acid for pregnant and lactating sows and newborn piglets, and is important for the growth and development of the fetus and neonate [9][10][11]. A high-fat diet and arginine supplementation were recently reported by Jobgen et al to differentially regulate gene expression and affect energy-substrate oxidation, redox state, fat accretion, and adipocyte differentiation in adipose tissue, and a beneficial effect of arginine on ameliorating diet-induced obesity in rats was demonstrated [33]. Dietary supplementation with arginine increased muscle gain and decreased subcutaneous fat deposition in growing-finishing pigs, and, arginine enhanced longissimus dorsi muscle protein, glycogen, and fat contents by 4.8%, 42%, and 70%, respectively [12].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, leucine activates the mammalian target of rapamycin to stimulate protein synthesis and inhibit intracellular proteolysis (Dillon 2012;Li et al 2011b), whereas methionine is the major donor of the methyl group to affect DNA and protein methylation in cells (Wang et al 2012). Notably, nutritional studies have shown that dietary supplementation with several AA (e.g., arginine, glutamine, glutamate, leucine, and proline) modulates gene expression and enhances growth of the small intestine and skeletal muscle (Geng et al 2011;Jobgen et al 2009;Wang et al 2008;Wu et al 2011a, b; Regulation of acid-base balance (e.g., renal ammoniagenesis from glutamine)…”
Section: Introductionmentioning
confidence: 99%